Capacidade de parasitismo de Trichogramma pretiosum em ovos de Trichoplusia ni em diferentes temperaturas - Carvalho, José Romário de; Pratissoli, Dirceu; Dalvi, Leandro Pin; Silva, Marcos Américo; Bueno, Regiane Cristina Oliveira de Freitas [UNESP]; Bueno, Adeney de Freitas (Universidade Estadual de Maringa, 2014)
Trichogramma spp. are egg parasitoids of various pest species of Lepidoptera including Trichoplusia ni, an important pest of plants in the genus Brassica. Of the climatic conditions that can impair Trichogramma spp. parasitism capacity, the temperature is critical. Thus, the objective of this research was to evaluate the parasitism capacity of Trichogramma pretiosum on eggs of T. ni at 18, 21, 24, 27, 30, and 33ºC; 70±10% RH; and 12/12 hours photophase (L/D). Fresh eggs of the host moth were offered to T. pretiosum daily. The parasitism rate varied between 8 and 11.4 eggs/female at the temperatures evaluated for the first 24 hours. The highest number of parasitized eggs per female occurred at 24ºC (53.0 parasitized eggs/female). The period of parasitism and the mean longevity of females were inversely related to the temperature. Temperature heavily influences the parasitism rate of T. pretiosum on eggs of T. ni, and the best overall performance of the parasitoid occurs from 24 to 27ºC.

Trichogramma spp. são parasitoide de ovos de várias espécies pragas de Lepidoptera incluindo Trichoplusia ni, uma importante praga de plantas do gênero Brassica. Das condições climáticas que podem influenciar a capacidade de parasitismo de Trichogramma spp., a temperatura é uma das principais. Portanto, o objetivo deste trabalho foi avaliar a capacidade de parasitismo de Trichogramma pretiosum em ovos de T. ni nas temperaturas de 18, 21, 24, 27, 30 e 33ºC; 70±10% UR; e 14/12h fotofase. Ovos frescos de T. ni foram oferecidos diariamente para T. pretiosum. A taxa de parasitismo nas primeiras 24h variou de 8 a 11,4 ovos/fêmea do parasitoide entre as temperaturas avaliadas. O maior número de ovos parasitados por fêmea ocorreu a 24ºC (53,0 ovos parasitados/fêmea). O tempo de parasitismo e a longevidade média dos parasitoides adultos foram inversamente relacionados à temperatura. Temperatura influência enormemente no parasitismo de T. pretiosum em ovos de T. ni, e os melhores resultados do parasitoide foram obtidos de 24 a 27ºC.
Parasitism capacity of Trichogramma pretiosum on eggs of Trichoplusia ni at different temperatures
Keywords: Insecta; Biological control; Horticultural plants; Insecta; Controle biológico; Horticultura